Self-care management education for diabetes mellitus patients based on disease perception and length of suffering - Zusana A. Sasarari; Rasi Rahagia; Suprapto Suprapto; M. Khalid Fredy Saputra (Edukasi Ilmiah Indonesia, 2025)
Diabetes mellitus is a chronic disease that requires comprehensive management and active participation from patients to prevent complications and improve quality of life. One of the most critical aspects of diabetes management is self-care, which encompasses diet regulation, regular physical activity, medication adherence, blood glucose monitoring, and stress management. However, patients’ perception of the disease and the length of time they have been suffering from it often influence their ability to implement effective self-care practices. This community service program aimed to provide self-care management education for patients with diabetes mellitus, tailored to their perception of the disease and the duration of their illness. The method used involved structured educational sessions, interactive discussions, and practical demonstrations tailored to patients’ levels of understanding and experiences in managing diabetes. Pre- and post-intervention assessments were conducted to evaluate changes in knowledge, attitudes, and perceived self-efficacy. The results indicated that patients with longer disease duration generally demonstrated higher awareness but also faced challenges in maintaining long-term self-care consistency. Meanwhile, newly diagnosed patients often underestimate the seriousness of diabetes, which affects their adherence to lifestyle modifications. The program successfully enhanced patients’ knowledge and motivated them to engage in sustainable self-care practices. Community-based education that considers disease perception and the length of suffering is therefore an effective strategy for empowering patients with diabetes mellitus to manage their health. This approach is expected to reduce complications, enhance overall well-being, and support public health initiatives in the management of chronic diseases